FRAZEOLOGIYA TILSHUNOSLIKNING ALOHIDA BO'LIMI SIFATIDA SHAKLLANISH TARIXI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article talks about the emergence of phraseology and its separation as a separate branch of linguistics, as well as the history of its development. In addition, the contribution of foreign scientists to this science, the valuable works created by Uzbek linguists in the field of science are given.
Keywords: phraseology, linguistics, ideomatic word, lexicology, Turkic studies, phraseology